Joaquim Tenreiro: arte, técnica e história do mobiliário brasileiro - Bleich, Marcia Campos (2017)
Joaquim Tenreiro, a carpenter born in Portugal, lived in Brazil since the year 1928, to whom is attributed a great contribution in the creation of the Brazilian Modern Furniture. The present work has as challenge to present a reading of his work as carpenter, designer and decorator and the reconstitution of his trajectory from his first work, developed for the residence of Francisco Inácio Peixoto, designed by Oscar Niemeyer in 1942, until the termination of his activities as furniture designer in 1968. The furniture and interiors of Joaquim Tenreiro, who bequeathed to posterity a vast work laden with the marks that witness the Modern Movement of Architecture and Design in Brazil, are analyzed in order to decode the creation of a language for the Brazilian furniture, followed by great Designers who have tracked his steps